Central-line–associated bloodstream infections and central-line–associated non-CLABSI complications among pediatric oncology patients. (27th March 2023) - Kelada, Aml S.; Foster, Timothy B.; Gagliano, Gregory C.; Worley, Sarah; Tang, Anne; Arakoni, Venkatraman A.; Foster, Charles B.
Abstract: Objective: To assess central venous catheter (CVC) harm in pediatric oncology patients, we explored risks for central-line–associated bloodstream infections (CLABSIs) and central-line–associated non-CLABSI complications (CLANCs). Design: Retrospective cohort study. Setting: Midwestern US pediatric oncology program. Patients: The study cohort comprised 592 pediatric oncology patients seen between 2006 and 2016. Methods: CLABSIs were defined according to Centers for Disease Control and Prevention (CDC)/National Health Safety Network (NHSN) definitions. CLANCs were classified using a novel definition requiring CVC removal. Patient-level and central-line–level risks were calculated using a negative binomial model to adjust for correlations between total events and line numbers. Results: CVCs were inserted in 62% of patients, with 175, 937 total catheter days. The inpatient CLABSI and CLANC rates were 5.8 and 8.5 times higher than outpatient rates. At the patient level, shared risks included acute myeloid leukemia (AML) and age <1 year at diagnosis. At the line level, shared risks included age <1 year at diagnosis, non-mediports, and >1 lumen. AML was a CLABSI-specific risk. CLANC-specific risks included non–brain-tumor diagnosis, younger age at diagnosis or central-line placement, and age <1 year at diagnosis or line placement. Multivariable risks were for CLABSI >1 lumen and for CLANC age <1 year at placement. Conclusions: Among patients with CVCs, CLABSI and CLANC rates were similar, higher among inpatients than outpatients. For both CLABSIs and CLANCs, infants and patients with AML were at higher risk. In both univariate and multivariate models, lines with >1 lumen were associated with CLABSIs and placement during infancy with CLANCs.